Significance and Meanings of Neurotic Level Anxiety - M Yu Norina; M S Pavlova (Peoples' Friendship University of Russia (RUDN University), 2011)
The article presents the results of the research carried out with the purpose of revealing the meanings of the neurotic level anxiety. It defines and describes the meanings of normal anxiety: living through life, confrontation; and also the meanings of pathological anxiety: avoiding, denial of difficulties; the feeling of powerlessness and unfulfillment; low involvement in the process of life.